The Dutch Lung Cancer Audit: Nationwide quality of care evaluation of lung cancer patients. (November 2020) - Ismail, R.K.; Schramel, F.M.N.H.; van Dartel, M.; Hilarius, D.L.; de Boer, A.; Wouters, M.W.J.M.; Smit, H.J.M.; ,
Highlights: The establishment of the DLCA-L led to insights and improvements in hospital care. The DLCA-L data visualize real-world use of systemic therapies. Real-world use of immunotherapy differs from trial setting. Abstract: Objectives: This study describes the initiation of the Dutch Lung Cancer Audit for Lung Oncology (DLCA-L) and reports the first results of three years of clinical auditing. Methods: The initiation, dataset, and data quality of the DLCA-L are described. For the analyses, all patients registered from 2017 to 2019 were included. Descriptive statistics were used to assess the first outcomes of the DLCA-L, including results from quality indicators, patient- and tumor characteristics, and the real-world use of immunotherapy. Results: The DLCA-L was initiated after the surgery and radiotherapy audit for lung cancer. In total, 33.788 NSCLC patients and 4.293 SCLC patients were registered in the DLCA-L from 2017 to 2019. Seventy-three (97 %) Dutch hospitals participated in the DLCA-L in 2019. The registry became nation-wide in 2020. The data quality improved over the years, with complete cases in 90 % of the NSCLC patients. In total, 15 quality indicators were established based on DLCA-L data to improve processes and clinical outcomes. An example of these quality indicators was brain imaging at diagnosis of stage III NSCLC patients, which increased from 80 % in 2017 to 90 % in 2019 and hospital variation was reduced. The DLCA-L provided data on immunotherapy use in stage IV NSCLC (n = 4.415) patients. These patients had a median age of 67 years and 11 % of the patients had an ECOG PS ≥ 2. The number of patients treated with immunotherapy in different hospitals varied between 2 patients to 163 patients per hospital. Conclusion: The DLCA-L has become a valuable and complete data source with national coverage in 2020. A high number of registered patients and limited missing data resulted in better insights into hospital processes and outcomes of lung cancer care. Quality indicators were, with success, used to establish improvements and minimize hospital variation. The DLCA-L also provides hospitals real-world information on the use of (systemic) therapies.